2005
DOI: 10.1191/1362168805lr161oa
|View full text |Cite
|
Sign up to set email alerts
|

Language aptitude and its relationship to instructional effectiveness in second language acquisition

Abstract: Experimental second language acquisition research typically investigates the effectiveness of instruction in terms of overall group gains. A particular instructional method may not, however, benefit all learners uniformly. This study, conducted in a New Zealand secondary school, establishes whether there is any relationship between the effectiveness of three instructional methods, and learner aptitude. Students (n = 60) were assigned to one of three groups (deductive instruction group, inductive instruction gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 34 publications
(35 reference statements)
9
131
3
1
Order By: Relevance
“…LAA, being relevant for pattern identification during SLA which involves analysing and processing new linguistic input (Skehan, 2002), is arguably the most important of the aptitude components when it comes to grammar learning: learners with a high degree of LAA are sensitive to grammatical structure of new languages and are able to make linguistic generalisations easily. SLA research has shown that LAA plays an important role in second language acquisition in a variety of contexts, including immersion (Harley & Hart, 1997), classroom (Erlam, 2005) and lab (Yilmaz, 2012) …”
Section: High Cognitive Skills For Grammar Learningmentioning
confidence: 99%
“…LAA, being relevant for pattern identification during SLA which involves analysing and processing new linguistic input (Skehan, 2002), is arguably the most important of the aptitude components when it comes to grammar learning: learners with a high degree of LAA are sensitive to grammatical structure of new languages and are able to make linguistic generalisations easily. SLA research has shown that LAA plays an important role in second language acquisition in a variety of contexts, including immersion (Harley & Hart, 1997), classroom (Erlam, 2005) and lab (Yilmaz, 2012) …”
Section: High Cognitive Skills For Grammar Learningmentioning
confidence: 99%
“…Although not immediately concerned with the notion of metalinguistic knowledge, Erlam (2005) found that, in adolescent L1 English learners of L2 French, deductive instruction involving explicit rule explanation, formfocused activities, output practice, and corrective feedback seemed to minimize the effects of individual learner differences in phonetic coding ability and language-analytic ability, operationalized by means of the wordsin-sentences subtest of the MLAT. By contrast, Ranta (2002) concluded that in adolescent L1 French learners of L2 English, a communicative classroom environment apparently could not counteract the effects of individual differences in language-analytic ability.…”
Section: L2 Proficiency Metalinguistic Knowledge and Language-analymentioning
confidence: 99%
“…More specifically, both grammatical sensitivity and inductive language learning ability are believed to play a part in the same L2 processing stages, that is, the identification and generalization of linguistic patterns (Skehan 1998(Skehan , 2002. In several recent discussions of the construct of aptitude, the notion of language-analytic ability in the sense of a learner's ability to identify and extrapolate linguistic patterns has been adopted (Ranta 2002;Dö rnyei and Skehan 2003;Erlam 2005). Hence, at a conceptual level, a primarily analytic component of aptitude comprising grammatical sensitivity and inductive language learning ability-as subsumed under the label of language-analytic ability-may be distinguished from the primarily memory-based components of phonetic coding ability and rote-learning ability.…”
Section: L2 Proficiency Metalinguistic Knowledge and Language-analymentioning
confidence: 99%
“…Aptitudetreatment interaction: General Reves, 1982;Wesche, 1981;Robinson, 1995Robinson, & 2002Erlam, 2005 aptitude information (profile) is not only desirable but also has tremendous pedagogical implications under different L2 learning conditions. & Newport, 1989;Dekeyser, 2000;Hart, 1997 & Younger learners tend to show higher correlations with memory components and older learners with analytical components.…”
Section: Componentsorientedmentioning
confidence: 99%